Design and simulation Automated Storage and Retrieval System (ASRS) using solidworks - Mior Hasafi, Nur Azidah Aishah (2020)
This paper presents the design and simulation of Automated Storage and Retrieval System (ASRS) using SolidWorks software. ASRS is a system usually used to ease the storage and retrieval of a lot of things at one place. In this project, the most basic form of ASRS is depicted which is single-unit load aisle captive ASRS. The human ability to imagine differs from one person to another thus to introduce ASRS to people who knows and are indifferent to it, imagination is discarded as this project presents the ASRS in the form of three-dimensional (3D). SolidWorks is used to design the system due to the software being able to offer designers a way to design in 3D and providesimulation of its movements using motion analysis. It is also used to analyze critical parts in the system using Simulation Xpress study.